ANALISIS PEMANFAATAN EARMARKING TAX DALAM MENINGKATKAN PENDAPATAN DAERAH STUDI PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA KENDARI - Asni, Nur; Kalsum, Auliah (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACTÂ This study aimed to investigate and describe about the use of earmarking tax on increasing the income on Kendari, 2014. This study used qualitative approach. The primer data was obtained from interview and the secunder data was obtained from the documentation of The Department of Management of The Local Financial and Assests of Kendari and all stakeholders in relevance to this present study. The data analysis of the study used descriptive analysis.The result of the study showed that the earmarking tax receipts of cigarette tax in Kendari 2014 amouned to Rp 2.295.027.448 or contribute approxiamately 0,20% of the total regional income. However, the benefit implementation is not appropriately maximal to the target spesifically in relevant to the impact of cigarette since the minimum socialization and transparency of fund information about the use of earmarking.Keywords: Earmarking Tax, Cigarette Tax.